Our stolen future: are we threatening our fertility, intelligence, and survival? A scientific detective story - Colborn, Theo; Dumanoski, Dianne; Myers, John Peterson (New York, 1997)
"…a book about the health and environmental threats created by man-made chemical contaminants that intefere with hormones in humans and wildlife. endocrine disrupting chemicals alter development of the fetus in the womb by interfering with the natural hormonal signals directing fetal growth. their impacts, sometimes not detectable until years or decades after exposure, include reduced disease resistance, diminished fertility and compromised intelligence and behavior. our stolen future tells the story of how endocrine disruption was discovered, how it works what it means, and how families can protect themselves and their communities, all in clear, simple language intended for a general audience...", from foreword by vice president Al Gore.